IDENTIFIKASI RUANG TERBUKA HIJAU (RTH) DI KAWASAN PERUMAHAN TAMAN MAPANGET RAYA KECAMATAN MAPANGET KOTA MANADO - Maks Bernard Krisifu; Zetly E. Tamod; Meldi T.M. Sinolungan (Universitas Sam Ratulangi, 2018)
ABSTRACT The aim of the study was to identify Green Open Space (GOS) at Taman Mapanget Raya (TAMARA) Residence Area of Mapanget Sub-district, Manado City. The method was a qualitative descriptive study, by using data in the forms of words, schemes and images. Result has found that, the Green Open Space (GOS) identification were based on: 1)Availability of GOS at TAMARA Residence of Mapanget Subdistrict, which was consisted of: GOS of Green Line (6,659 m2), GOS of City Garden (3,828 m2), GOS of Residences Yard (1,249 m2), GOS of People Estate (8,449 m2), GOS of City Forest (14,389 m2), and GOS of Agriculture (10,993 m2), has found in amount of 45,567 m2, or almost 4.6 Ha from the total land area of TAMARA Residence (509,303 m2, or 50.9 Ha). The percentage of Public GOS at TAMARA Residence was 8.9% from the total land area of this residence, whereas the percentage of this Public GOS was 0.09% from the GOS of Mapanget Sub-district, which showed that the Public GOS at this residence has not been fulfilled; 2)Land physical characteristics and kinds of plant at GOS location of TAMARA Residence were flat until slope gently in topography, parent material of alluvial, flood land plain, colluvium, sands, sandy rocks, and volcanic breccia, and some kinds of plants, were: Coconut, Banana, Corn, Sedge-grass, others; and 3)Soil chemical characteristics were consisted of: organic matter more than 2%, CEC in the medium category, the contents of K and P in criteria low to high, and pH in criteria of low (rather acid) to high (rather base). Keywords : Identification, Green Open Space, Residences Area